Dynamics on the manifold: Identifying computational dynamical activity from neural population recordings. (October 2021) - Duncker, Lea; Sahani, Maneesh
Abstract: The question of how the collective activity of neural populations gives rise to complex behaviour is fundamental to neuroscience. At the core of this question lie considerations about how neural circuits can perform computations that enable sensory perception, decision making, and motor control. It is thought that such computations are implemented through the dynamical evolution of distributed activity in recurrent circuits. Thus, identifying dynamical structure in neural population activity is a key challenge towards a better understanding of neural computation. At the same time, interpreting this structure in light of the computation of interest is essential for linking the time-varying activity patterns of the neural population to ongoing computational processes. Here, we review methods that aim to quantify structure in neural population recordings through a dynamical system defined in a low-dimensional latent variable space. We discuss advantages and limitations of different modelling approaches and address future challenges for the field. Highlights: Neural activity is often confined to low–dimensional activity manifolds. Dynamical systems can connect activity manifolds to underlying circuit computation. We highlight data-analysis approaches to study computation through dynamics. Future directions include linking data analysis to artificial network models.